Formula for a Comprehensive Year Four Student-Run Free Clinic Elective - Christopher LaJeunesse; Ashika Bains; Rebecca Fisher; Margit Chadwell; Juliann Binienda (Journal of Student-Run Clinics, 2016)
Many student-run clinics offer electives for professional students. They provide additional clinical experience and exposure to practice management. Since it began five years ago, Wayne State University School of Medicineâ€™s Robert R. Frank Student-Run Free Clinic offers its fourth-year medical students with an innovative and comprehensive elective.  Twenty-five students have completed this elective. Four pillars create the foundation of this unique learning environment: clinical care, leadership/mentorship, teaching, and scholarship. We present a blueprint for professional schools to shape their elective to become truly student-run and to give advanced students a rich capstone experience preparing them for future training.